Digitizing Medieval Manuscripts - Endres, Bill (Arc Humanities Press, 2019)
What does it mean to digitize a medieval manuscript? This book examines this question by exploring a range of advanced imaging technologies. The author focuses on the relationship between digital technologies and the complex materiality of manuscripts and the human bodies that engage them.The chapters explore imaging technologies, interfaces to present digital surrogates, and limitations to and enhancements through the digital, plus historical photographs. Essential reading for all those involved in manuscript digitization projects in both scholarly and cultural heritage contexts
10.1515/9781942401803
Keywords: 3D.; St Chad Gospels; advanced imaging technologies; digital humanities; digital methods; ethics; medieval manuscripts; multispectral; reflectance transformation imaging; sacred artifacts; LITERARY CRITICISM / Medieval